Self-deception in Narration - Faulerova, Lucie (Bohemica Olomucensia, 2016)
The present paper is the first part of the study that deals with unreliable narration as both an interpretative frame and a specific narrative perspective. It attempts to formulate the basic problems concerning the difficulties that occur when some of the well-estabshiled theses of unreliable narration are applied to analyses of particular narratives and discuss the problem of ``self-deception'' in narration. In this part of the study, the problems of self-deception have been only outlined as part of the analyses of the novels Grandhotel by Jaroslav Rudis and Fight Club by Chuck Palahniuk.
Keywords: narrator; unreliable narration; self-deception; narrative; narratology; interpretative frame; narrative perspective; fictional world; Grandhotel; Klub rvacu